PERAN TENAGA MEDIS DALAM PELAKSANAAN PROGRAM UNIVERSAL COVERAGE DI PUSKESMAS BAHU KOTA MANADO - KONDOY, EKA ALVITA; Posumah, Johnny Hanny; Londa, Very Yohanis (Sam Ratulangi University, 2017)
Abstract :The purpose of this study is to determine the role of medical personnel in providing health services to patientsparticipating in Universal Coverage program at Bahu Manado Health Center.This research uses qualitative research method. Informant research as much as 8 (eight) informant thatconsist of 1 head of health center, 1 Officer Administration, 3 doctors and 3 community of universalcoverage program participants. Data collection techniques used are Interview Techniques, ObservationTechniques / Observations, and Documentation Techniques. And Data Analysis Techniques used are DataReduction, Data Channel, and Withdrawal Conclusion.Based on research that can be drawn conclusion as follows: First, promotive service has been implementedby medical personnel with health education and health promotion provided directly and indirectly to thecommunity. Second, preventive services provided through immunization and fogging. Third, Curativeservice in the form of medication business for patient to reduce pain and or relieve pain suffered by patientwith expense borne by Manado city government for society of universal coverage participants. Fourth,rehabilitative services have also been provided although not as much as in hospitals, such as gymnastics torestore muscle function for newborn patients.Keywords: Role of Medical Personnel, Universal Coverage